Vague Separation - Ramya Swetha, R; Anitha, T; Amarendra Babu, V (International Journal of Engineering and Technology, 2018)
In this paper we are introducingÂ VT1 space, vague haussdorff space (VT2) and then we derive every vague subspace ofÂ VT1 space is VT1 and also for VT2. And also we derive the Cartesian product of two vague closed sets is also vague closed set in the vague product topological space X x Y .Finally we define Vague limit point, Vague isolated point, Vague adherent point, Vague perfect, Vague derived set, vague exterior and also derive some theorems on this .